Cyber Resilience Strategy as A Key Element of Building A GIS Business Continuity Plan - Jerzy STANIK; Maciej KIEDROWICZ (Communications of International Proceedings, 2023)
The article defines and analyzes two basic concepts: cyber resilience strategy and business continuity plan in relation to GIS systems. To combine cyber resilience with the GIS business continuity system, in the context of the landscape of possible cyber threats and uncertainties, we used several aspects: cyber resilience framework and standards, business continuity team, a package of necessary documentation for ISO 22301:2019, technologies and tools supporting the implementation of the process ensures business continuity and a set of indicators for measuring GIS cyber resilience in the light of ensuring its business continuity. In each of these aspects, differences can be noticed in the approach to both the GIS cyber resilience strategy and the business continuity plan.
Keywords: cyber resilience; GIS; business continuity plan; cyber resilience system model